Authoritarian regimes and the co-optation of Islam: Kazakhstan and Russia - Fradkin, R (2019)
National and subnational authoritarian regimes with Muslim majorities prefer to co-opt rather than repress Islam in order to bolster their legitimacy, limit bargaining partners, deter mobilization, and gather information. Authoritarian regimes also elect to co-opt other potential sources of opposition besides religion due to similar incentives. Religion, however, is a unique source of potential opposition given its high salience relative to other forms of identity. Repression or overt co-optation of the majority religious identity holds a higher potential to foster an opposition movement based on religious identity. In order to deter this threat, national and subnational regimes frequently create a separate religious institution for Islam. Kazakhstan, a national authoritarian regime, and Tatarstan, Russia, a subnational authoritarian regime, both attempt to co-opt the majority religious group, Islam, through quasi-governmental agencies. Quasi-governmental agencies reduce transparency and provide a semblance of official distance between co-optation efforts and the regime. However, the different layer of institutional structures between national and subnational authoritarian regimes spurs each type of regime to pursue different strategies. Given the regime juxtaposition between Tatarstan and Russia, Tatarstan more frequently pursues co-optation through unofficial and extra-legal means. Alternatively, a higher level of institutions does not exist in Kazakhstan. Thus, there is a higher degree of harmony between the law and policies on religion. In addition to using a quasi-governmental agency, both regimes attempt to securitize Islam by framing regime associated religious sources as the panacea to extremism and other negative influences. Muslims in Kazakhstan were more likely than Muslims in Tatarstan to report using religious sources approved by the regime. This is likely because Kazakhstan had a wider array of tools at hand to co-opt Islam. However, a majority of Muslims in neither case cited securitization narratives to justify why they chose to use governmental religious sources.